2018
DOI: 10.18632/oncotarget.24745
|View full text |Cite
|
Sign up to set email alerts
|

Human cancer cells utilize mitotic DNA synthesis to resist replication stress at telomeres regardless of their telomere maintenance mechanism

Abstract: Telomeres resemble common fragile sites (CFSs) in that they are difficult-to-replicate and exhibit fragility in mitosis in response to DNA replication stress. At CFSs, this fragility is associated with a delay in the completion of DNA replication until early mitosis, whereupon cells are proposed to switch to a RAD52-dependent form of break-induced replication. Here, we show that this mitotic DNA synthesis (MiDAS) is also a feature of human telomeres. Telomeric MiDAS is not restricted to those telomeres display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 26 publications
5
85
0
Order By: Relevance
“…These findings suggest that a temporal separation between DNA synthesis and chromosome segregation does not seem to be a strict rule for eukaryotic cells. However, DNA synthesis outside S phase is particularly prevalent in cells exhibiting aneuploidy (58,59), suggesting it may be less effective at maintaining genome integrity. Here, we provide evidence that L. major, a eukaryotic organism with constitutive mosaic aneuploidy (at least in parasite cells derived from, or proliferating in the insect vector) (38,60), achieves full genome duplication using DNA synthesis outside S phase, including G2/M and G1.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that a temporal separation between DNA synthesis and chromosome segregation does not seem to be a strict rule for eukaryotic cells. However, DNA synthesis outside S phase is particularly prevalent in cells exhibiting aneuploidy (58,59), suggesting it may be less effective at maintaining genome integrity. Here, we provide evidence that L. major, a eukaryotic organism with constitutive mosaic aneuploidy (at least in parasite cells derived from, or proliferating in the insect vector) (38,60), achieves full genome duplication using DNA synthesis outside S phase, including G2/M and G1.…”
Section: Discussionmentioning
confidence: 99%
“…APBs have been proposed to play a critical role in ALT by clustering telomeres and DNA repair factors together, thus concentrating substrates and enzymes required for recombination-based telomere elongation (Henson et al 2002;Cesare and Reddel 2010;Chung et al 2011;Chung et al 2012;Min et al 2019;Verma et al 2019). In agreement with this hypothesis, it has recently been shown that telomeres can be elongated during mitosis in APB-like foci in a process termed mitotic DNA synthesis MiDAS (Ozer et al 2018;Min et al 2019). Moreover, depletion of PML by siRNA has been shown to reduce telomere elongation (Osterwald et al 2015).…”
Section: Introductionmentioning
confidence: 90%
“…When we treated Pol η-depleted ALT cells with low dose of aphidicolin followed by EdU pulse, EdU positive newly synthesized DNA was observed on telomeric sequences of metaphase chromosomes, demonstrating that MiDAS is also a feature of human telomeres [24] ( Figure 1C). In fact, a recent work reported that telomeric MiDAS seems also to occur in cells maintaining their telomeres by the telomerase [29].…”
Section: Why the Cells Use Midas?mentioning
confidence: 99%
“…Therefore, RAD52 appears to hold a cardinal function at an SLX4-dependent step in CFS-associated MiDAS prior to the involvement of MUS81 or POLD3 (see model in Figure 2). At telomeres, MiDAS resembles to CFS-related MiDAS as it requires also RAD52 [29] but it does not require the MUS81-EME1 endonuclease, suggesting that another nuclease might be involved or MiDAS events do not all require an initial endonuclease cut.…”
Section: Mechanisms and Molecular Actors Involved In Midasmentioning
confidence: 99%